MYTUTOR SUBJECT ANSWERS

247 views

Solve the Simultaneous Equations -3X + 4Y=11 & X-2Y = -5 to find the values of X and Y

Simultaneous Equations are equations involving 2 or more unknowns that have the same value in each equation. The aim is to eliminate all but one unknown. This will then allow us to find the value of the non eliminated unknown. From this any other unknowns can be found. There are 2 main methods we can use to solve these problems:

A) Solving by Elimination.

The first step is to label the equations

(1) -3X +4y= 11

(2)    X - 2Y= -5

You must then manipulate the equations in such a way that the coefficient of one of the unknown variables is the same value in both equations. 

In this example, the equations will be manipulated in order to obtain equal values for the coefficient of Y in both equations

Equation (2) multiplied by 2

(1):        -3X +4y= 11

(2) x 2:   2X -4Y= -10

We can now add both equations together in order to eliminate the Y unknown.

(1) + (2) x 2

(1):        -3X +4y= 11

              +

(2) x 2:   2X -4Y= -10

-X= 1

Divide both sides by -1

X= -1

In order to find the value of Y, substitute X= -1 into any one of the original equations.

Substituting X= -1 into  equation (2):      X- 2Y = -5

  

-1 -2Y = -5

-2Y = -4

Divide both sides by -2

Y=2

Therefore we have solved the simultaneous equations and obtained the answer of X= -1 and Y=2.

B) Solving by Substitution

The first step here is making one of the unknown variables the subject of one of the equations.

Using equation (2): X- 2Y= -5 ——> X= -5 -2Y

You must then substitute this value for the unknown into the other equation.

Substituting X= -5- 2Y into Equation (1): -3X + 4Y =11

-3 (-5+ 2Y) +4Y =11

Expand the brackets

15 -6Y + 4Y =11

Group like terms together

15-11 = 6Y-4Y

4= 2Y

Divide both sides by 2

Y=2

To find the value of X, substitute  Y=2 into X= -5- 2Y

X= -5 - 2(2)

X= -1

Therefore we have solved the simultaneous equations and obtained the answer of x= -1 and y=2.

Emehakon U. GCSE Maths tutor, GCSE Law tutor, A Level Law tutor

7 months ago

Answered by Emehakon, a GCSE Maths tutor with MyTutor


Still stuck? Get one-to-one help from a personally interviewed subject specialist

318 SUBJECT SPECIALISTS

£18 /hr

Emily L.

Degree: Law (Bachelors) - Durham University

Subjects offered: Maths, English Literature+ 1 more

Maths
English Literature

“I am a first year undergraduate reading Law at Durham University. Prior to this, I attended the Tiffin Girls' School in Kingston upon Thames where I studied English Literature, Chemistry and Fine Art at A2 Level (with additional Mathe...”

£18 /hr

Daniel S.

Degree: MEng Mechanical Engineering (Masters) - Exeter University

Subjects offered: Maths, Further Mathematics

Maths
Further Mathematics

“Hi, I'm Dan and I am currently on the Masters Mechanical Engineering course at Exeter University. I studied Maths, Further Maths and Physics at A-level and recieved A*AA grades for them. I love helping people understand maths and I fi...”

MyTutor guarantee

£18 /hr

Dhulaxy M.

Degree: Biological Sciences (Bachelors) - University College London University

Subjects offered: Maths

Maths

“I am currently a first-year Biology student at University College London. I love that my course brings in aspects of the other ‘science’ subjects, especially Maths! I have volunteered in environments like the library and nursing home ...”

MyTutor guarantee

About the author

£18 /hr

Emehakon U.

Degree: Law (Bachelors) - Durham University

Subjects offered: Maths, Law

Maths
Law

“I am a Law student at Durham University. I have always had a passion for finding solutions to problems. (Both in a practical and Mathematical sense!) . I'll be sure to utilize that passion in order to give you the best outcome possibl...”

MyTutor guarantee

You may also like...

Other GCSE Maths questions

How would I solve this set of simultaneous equations using the elimination method?

How is frequency density calculated?

A circle with centre C has equation x^2 + y^2 + 2x - 6y - 40 = 0. Express as (x - a)^2 + (y - b)^2 = d.

Expand and simplify (3x+2) (x-5)

View GCSE Maths tutors

Cookies:

We use cookies to improve our service. By continuing to use this website, we'll assume that you're OK with this. Dismiss

mtw:mercury1:status:ok